2011
DOI: 10.1287/opre.1100.0871
|View full text |Cite
|
Sign up to set email alerts
|

OR PRACTICE—Production Planning with Patterns: A Problem from Processed Food Manufacturing

Abstract: Based on our work with ConAgra Foods (http://www.conagrafoods.com), a leading U.S. food manufacturer, we study a large-scale production-planning problem. The problem incorporates several distinguishing characteristics of production in the processed-food industry, including (i) production patterns that define specific combinations of weeks in which products can be produced, (ii) food groups that classify products based on the allergens they contain, (iii) sequence-dependent setup times, and (iv) manufacture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…Such results show that this manual heuristic did accommodate the need for mix flexibility and minimisation of production costs in Baking Company. The theoretical savings calculated for the production cycles at Baking Company are slightly higher than other research studies which used production cycles, such as the 15% reduction in setup and inventory costs found by Mehrotra et al (2011) using their optimisation model. A study of product wheels in the process industry showed mixed results as to the impact of scheduling on changeover time, increasing the time in some cases and decreasing time in others (Wilson & Ali, 2014).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Such results show that this manual heuristic did accommodate the need for mix flexibility and minimisation of production costs in Baking Company. The theoretical savings calculated for the production cycles at Baking Company are slightly higher than other research studies which used production cycles, such as the 15% reduction in setup and inventory costs found by Mehrotra et al (2011) using their optimisation model. A study of product wheels in the process industry showed mixed results as to the impact of scheduling on changeover time, increasing the time in some cases and decreasing time in others (Wilson & Ali, 2014).…”
Section: Resultscontrasting
confidence: 55%
“…However, based on the application example of Baking Company in this study, it can be concluded that the method should be reserved for small problems where few MTS items are required to be integrated into the product wheel. The other optimisation models presented in Table 1 which utilised operations research methods to solve the issues of natural sequencing via schedule blocks might be more suitable for solving applications with higher variety (Bilgen & Günther, 2010;Günther et al, 2006;Mehrotra et al, 2011;Mendéz & Cerdá, 2002;Pinedo, 2009). Just like the product wheel, the operations research production cycles aim to increase production efficiency by using pre-defined sequences of production orders.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence-dependent ELSP Ever since the ELSP was first introduced by Rogers (1958), a large number of heuristics, among them the socalled common-cycle, basic-period, and varying-lot-sizes approaches, have been proposed (see, e.g., the reviews given in Elmaghraby, 1978;Davis, 1995;and Carstensen, 1999). Although sequence-dependent setup times and costs are reported to be prevalent in most practical applications (see, e.g., Monkman et al, 2008 andMehrotra et al, 2011), the vast majority of the ELSP-related research concentrates on the special case of sequence-independent setup times and costs. Early exceptions like Maxwell (1964), Sing and Foster (1987), and Inman and Jones (1993) considered very restrictive forms of setup times.…”
Section: Related Literaturementioning
confidence: 99%
“…Both topics are relevant for food and agroindustries, particularly to the first as the industrial capacity and cost can be substantially modified due to changes in the production planning. Some studies have addressed specifically the operations scheduling in food and agro-industries, for instance: Doganis and Sarimveis (2007) proposed a mixed integer model for production scheduling in a single production line of yogurt; Simpson and Abakarov (2009) optimized the scheduling of thermal process in canned food industry; Toso et al (2009) approached the production scheduling in an animalfeed company; Ferreira et al (2010) dealt with the production lot-sizing and scheduling in the beverage industry; Kopanos et al (2011Kopanos et al ( , 2012 coped with the production planning in semicontinuous food industries; Mehrotra et al (2011) conducted a study of production planning with patterns in a large company in USA; Amorim et al (2012) formulated models integrating production and distribution planning of perishable goods; Wauters et al (2012) also approached the production scheduling for the food industry in real contexts.…”
Section: Introductionmentioning
confidence: 99%